2013
DOI: 10.1074/jbc.m112.442012
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Biophysical Properties of a Putative Hub Protein Expressed by Vaccinia Virus

Abstract: Background: Vaccinia protein H5 is a multifunctional protein involved in several aspects of viral replication. Results: H5 is a nucleic-acid binding, elongated rod-like tetramer with an instrinsically disordered N terminus and an ␣-helical C terminus. Conclusion: H5 functions as a hub protein in vaccinia virus replication linking otherwise unique viral processes. Significance: Understanding the mechanism of H5 function in vaccinia virus replication is crucial for studying vaccinia biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…In support of H5's contribution to transcription, it has also been shown to stimulate late transcription in a semipurified in vitro assay (54). Germane to each of these findings, the work of D'Costa, Condit, and colleagues has confirmed that the purified H5 protein exhibits nucleic acid binding activity, with the highest affinity being observed for dsDNA and double-stranded RNA (dsRNA) (K d s [dissociation constants] ϭ 12 and 14 nM, respectively) (53).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In support of H5's contribution to transcription, it has also been shown to stimulate late transcription in a semipurified in vitro assay (54). Germane to each of these findings, the work of D'Costa, Condit, and colleagues has confirmed that the purified H5 protein exhibits nucleic acid binding activity, with the highest affinity being observed for dsDNA and double-stranded RNA (dsRNA) (K d s [dissociation constants] ϭ 12 and 14 nM, respectively) (53).…”
Section: Discussionmentioning
confidence: 70%
“…H5 is an abundant multifunctional protein that has been reported to interact with components of the DNA replication machinery as well as the postreplicative transcriptional machinery (24,25,28,30). In addition, the H5 protein copurifies with and may be associated with an enzymatic activity capable of processing the 3= termini of a subset of postreplicative viral mRNAs (53). In support of H5's contribution to transcription, it has also been shown to stimulate late transcription in a semipurified in vitro assay (54).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…H5 is a constitutively expressed multifunctional nucleic acid binding protein involved in post-replicative transcription and mRNA processing (Cresawn and Condit, 2007; D’Costa et al, 2008; Kovacs and Moss, 1996), genome replication (D’Costa et al, 2010) and virion morphogenesis (DeMasi and Traktman, 2000). Moreover, biochemical and biophysical properties suggest that the H5 protein is intrinsically disordered and may be a “hub” protein (Kay et al, 2013). Although the late transcription factor cell line was successfully used to express reporter genes with late promoters, we have been unable to use it for isolation of a VACV late transcription factor deletion mutant.…”
Section: Discussionmentioning
confidence: 99%